(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
To enhance student satisfaction, hotel management schools are expected to play a key role in assessing service quality. Student satisfaction is a metric that assesses a student’s perceptions and expectations of a service given by the hotel industry. Hospitality is one of the best venues for students to develop their skills, advance their careers, and realize their full potential, which implies that the service of hotel operations must be of high quality. The global awareness of quality service delivery in hotel operations has grown significantly. Several studies have been undertaken over the years to assess student satisfaction and service quality (Yilmaz & Gurbuz, (2018); Pedro, Mendes, & Lourenço, (2018); Tijjani, (2019); Weerasinghe & Fernando, (2018), but this appears to be the first student satisfaction research. As a result, the study discovered a knowledge gap that has to be filled. This study evaluates service quality delivery regarding student satisfaction at a hotel operation to promote customer service and maintain the institution’s reputation. It will allow administrators to continually improve the quality of service provided to students in the hotel industry and assist in transmitting a desire for excellence, integrity, and excellent service. The main instrument used is survey questionnaires through Google Drive to gather the data needed to answer questions about hotel qualifications using different online platforms. The Researchers gathered information from Grade 12 students in Home Economics from the Bestlink College of the Philippines during the academic year 2021-2022. The study population under Home Economics is the Hotel Operation (HO). The respondents of this study will be selected from the four sections of the Grade 11 and Grade 12 Home Economics strand specializing in Hotel Operations (HO) who are studying in Bestlink College of the Philippines during the school year 2021-2022. The researchers selected 50 students from the population to survey online questionnaires distributed to those students taking up the given strand. The methods researchers used to conduct the survey were given a questionnaire according to the findings of the student’s performance. The question "Dealing with clients and customers politely and helpfully" has the greatest percentage of 4.54, and the question "A comparison of customer expectations with service performance" has the lowest percentage of 4.04. According to the students’ performance findings, the question "Confidence" has the highest percentage of 4.58, and the question "Valuing their feedback and transmitting clear messages" has the lowest percentage of 4.52. According to the student’s responses to the questions "Has a clean and laundry smell pleasant?" and "Good room service in a hotel by which meals or drinks are given for the guests," 4.58 has the greatest percentage. According to this study, students will better understand the significance of a quality service that they will remember for a long. In this study, we as the researchers assume that this research will help us to discover a study of student’s perceptions of the effect of service quality in hotel operations. Even students’ feedback will be necessary on hotel operations since they are still customers. We assume that this study will help hotels improve their hotel operations and services.